2023
DOI: 10.3390/biomedicines11061542
|View full text |Cite|
|
Sign up to set email alerts
|

Physiological Basis for Using Vitamin D to Improve Health

Abstract: Vitamin D is essential for life—its sufficiency improves metabolism, hormonal release, immune functions, and maintaining health. Vitamin D deficiency increases the vulnerability and severity of type 2 diabetes, metabolic syndrome, cancer, obesity, and infections. The active enzyme that generates vitamin D [calcitriol: 1,25(OH)2D], CYP27B1 (1a-hydoxylase), and its receptors (VDRs) are distributed ubiquitously in cells. Once calcitriol binds with VDRs, the complexes are translocated to the nucleus and interact w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(63 citation statements)
references
References 174 publications
1
62
0
Order By: Relevance
“…Vitamin D imposes a plethora of beneficial biological actions by mediating numerous endocrine and peripheral target cell functions. Skin, the location where vitamin D 3 synthesis takes place, also benefits from the protective mechanisms of vitamin D in mitigating the impact of skin photoaging [5,17,19,35].…”
Section: Vitamin D Against Photo-damagementioning
confidence: 99%
See 3 more Smart Citations
“…Vitamin D imposes a plethora of beneficial biological actions by mediating numerous endocrine and peripheral target cell functions. Skin, the location where vitamin D 3 synthesis takes place, also benefits from the protective mechanisms of vitamin D in mitigating the impact of skin photoaging [5,17,19,35].…”
Section: Vitamin D Against Photo-damagementioning
confidence: 99%
“…Calcitriol can also be generated within peripheral target cells, functioning as a localized cytokine and a signaling molecule. The active 1,25(OH) 2 D that gets circulated through the bloodstream exerts its biological actions by binding to the vitamin D receptor (VDR) in the tissues through genomic and non-genomic pathways [5]. The generation of calcitriol from sunlight exposure and dietary sources is illustrated in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vitamin D is an elemental membrane-associated protein for its nongenomic products (communication passageways) [ 67 - 69 ]. Multiple studies revealed that vitamin D is responsible for a broad range of physiological functions [ 50 , 70 , 71 ] because it regulates the expression of many genes and their biotic course [ 72 , 73 ]. It has been reported that Vitamin D exerts a straightforward influence on the epigenome and the manifestation of over 1000 genes in utmost hominoid tissues and cell categories [ 72 ].…”
Section: Introductionmentioning
confidence: 99%